Pelatihan Video Editing untuk Siswa dan Pemuda dalam Industri Kreatif Digital - Rudi Kurniawan; Ryan Hamonangan; Hilda Novia Ramadani; Ibnu Fajri (AMMA : Jurnal Pengabdian Masyarakat, 2022)
In the rapidly growing digital era, the need for skills in the creative industry is very important, especially in the field of video editing. Video editing training for students and youth aims to improve competence and practical skills that are relevant to current industry needs. This training activity was organized by Karang Taruna Kelurahan Lolu Selatan, in collaboration with the Digital Talent Indonesia Course and Training Institute (LKP), and targeted students and youth in Palu City who have an interest in digital creative fields. The training method used a hands-on approach with materials covering the basics of video editing, introduction to software, shooting techniques, and audio visual editing. The results of this training showed an increase in participants' knowledge and skills in using editing software and understanding the video production process. In addition, participants also obtained certificates as a form of recognition of the competencies obtained. This program is expected to be the first step in preparing the younger generation to compete in the world of work, especially in the creative industry sector. In conclusion, video editing training not only provides the benefits of technical skills, but also encourages creativity, innovation, and sustainable youth empowerment.